Determining Critical Ground Motion Parameters for Damage Prediction in Reinforced Concrete Frame Existing Buildings - Tanja Kalman Šipoš; Adriana Brandis; Uroš Bohinc; Uroš Ristić (Applied Sciences)
This study aimed to identify the critical ground motion parameters that lead to structural damage and assess their impact on the nonlinear responses of buildings. The analyses are carried out using a calibrated numerical model that was acquired within the ICONS experimental framework that represents reinforced concrete (RC) structures constructed before seismic design regulations were enforced. For the analysis, 30 seismic records were chosen based on magnitude (M), epicentral distance (R), and peak ground acceleration (PGA) for two high seismic activity areas that were observed. Eleven parameters are categorized, traditional metrics, energy-based, spectrum-based, duration-based, and fundamental metrics, and examined based on their main attributes. The results showed a strong relationship between certain seismic properties and the maximum interstory drifts of building as a damage prediction parameter. Peak ground velocity (PGV), specific energy density (SED), and Housner Intensity (HI) were found to be the most important variables in assessing the correlation with possible structural damage. Therefore, the assessment of structural damage based on nonlinear dynamic analysis should primarily incorporate PGV with the possible addition of energy- and spectrum-based metrics as the most reliable ground motion parameters for the selection of earthquake records for time history analysis.